Lokakarya Aplikasi Mutiara Medan Plus Bagi Masyarakat - Siska Evi Martina; Awidiyah; Alexander F.K Sibero; Donal Nababan (Jurnal Pengabdian Nasional (JPN) Indonesia, 2023)
HIV, or Human Immunodeficiency Virus, is a virus that damages the cells of the immune system that protect the body from disease. Therefore, when damage reduces the number of these cells, the body becomes more susceptible to infections and other illnesses. An HIV test is a test that detects HIV infection in a person's body. This time, a team from Sari Mutiara University in Indonesia created an application covering HIV/AIDS, 'Muara Medan Plus'. B. What is HIV, signs, and symptoms, how it is transmitted, what complications, and what to do if you are exposed or infected with HIV? The methods used in this article are qualitative. This application uses several theories to explain HIV and HIV rapid tests. After explaining about HIV and rapid tests and application, we explained the importance of HIV tests to the participants/community to learn more about HIV, download and use the application "Mutiara Medan Plus" and understand.